Impacto de la comunicación televisiva en el desarrollo cultural de los habitantes del Sector Fumisa, Cantón Buena Fe, año 2019 - Mendoza Peña, Yaira Cecibel (2019)
The value of television as a learning tool has always been demonstrated by local and national channels of open signal or paid television. People learn several things through image and sound, someone can be instructed in a negative or positive way with a television program. Therefore, the cultural television training in the inhabitants of the Fumisa sector of the Buena Fe Canton seeks to empower the culture, highlight the cultural field in all entities or states, therefore, it will always be linked to beneficial content for all viewers who serve for education and cultural development of society. Ecuadorian, national, local and foreign television incorporates within its programming grids contents that transmit norms, values or concepts in positive or negative. However, not everything that contains positive concepts can be called cultural television, it is for this reason that it is difficult to distinguish the programming that truly contributes to the cultural development of society. The professional in social communication or journalist can differentiate the contents of a program because it analyzes it from different points of view, but the current society does not. All efforts are made to make television cease to be a means of communication only aimed at entertainment and fun and become a tool for understanding and learning; Stop being an attraction of consumerism, so that it really becomes a public service of general interest and a medium full of values and virtues while maintaining our roots and where we are to enhance our culture. At present it does not matter if the efforts come from the state or private entities, the important thing is to assume that responsibility and commitment to the cultural, educational and social growth of Ecuadorians. Television is the only medium of the multimedia generation, from the middle class down and they are the great beneficiaries where awareness and responsibility must be generated.